PENGARUH UKURAN PERUSAHAAN, UKURAN DEWAN KOMISARIS DAN SENSITIVITAS INDUSTRI TERHADAP PENGUNGKAPAN CORPORATE SOCIA RESPONSIBILITY PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI TAHUN 2014-2016 - Yunina, Yunina; Eftiana, Neny (Department of Accounting, Faculty of Economics & Business, 2017)
This study aims to determine the effect of the size of the company, size of the board of commissioners and industrial sensitivity to the disclosure of corporate social responsibility partially and simultaneously. The data of this study were taken from 87 observations. The number of samples used in this study was 29 LQ-45 companies listed on the IDX in 2014-2016. The samples were taken by using purposive sampling technique. The method of data analysis used in this study was multiple linear regression analysis. The result of the research showed that size of company significantly influenced the disclosure of corporate social responsibility with significance level by 0,021, while size of board of commissioners did not significantly influence the disclosure of corporate social responsibility with the value of significance by 0,621, but industry sensitivity has significant influence to corporate social responsibility disclosure with a significant value of 0,010. The simultaneous test showed that firm size, board size and industry sensitivity simultaneously and significantly influenced the disclosure of corporate social responsibility significantly by 0,004. The GMS members who have the authority to propose, appoint and dismiss the board of commissioners should consider the candidates of the board of commissioners to be proposed, and the further research should expand the object of research and develop other factors that can affect the disclosure of corporate social responsibility such as foreign ownership, growth company, good corporate governance (GCG) practices and several other factors.